Perovskite photovoltaic device based on conductive adhesive bonding and preparation method thereof
By using the π-π interaction between the conductive adhesive layer and the self-assembled single molecule layer in perovskite photovoltaic devices, the problem of insufficient contact quality between the perovskite layer and the hole transport layer is solved, and the photoelectric conversion efficiency of the device is significantly improved and stability, achieving efficient interface modification effect.
Patent Information
- Application Number
- CN202411314207.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-20
AI Technical Summary
During the preparation of perovskite photovoltaic devices, the quality of interface contact between the perovskite layer and the hole transport layer affects the performance and stability of the device, and traditional interface modification methods are difficult to effectively improve interface stability and long-term efficiency.
Using conductive glue as adhesive, through the π-π interaction between the self-assembled single-molecular layer and the perovskite layer, the interface defect is passivated, and a stable conductive glue layer is constructed to optimize the contact between the buried interface and improve the charge transfer efficiency. .
The overall performance of perovskite photovoltaic devices has been significantly improved, and the photoelectric conversion efficiency and stability have been improved. The unprocessed devices have maintained an initial efficiency of 97.3% after 1200 hours, and the photoelectric conversion efficiency has reached 25.59%.
Smart Images

Figure CN119317295A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite photovoltaic devices, and in particular to a perovskite photovoltaic device based on conductive adhesive bonding and a preparation method thereof. Background Art
[0002] With the rapid development of perovskite solar cell technology, perovskite materials have shown broad application prospects in the photovoltaic field due to their high photoelectric conversion efficiency, low cost and convenient preparation process. However, in the preparation process of photovoltaic devices, the interface contact quality between the perovskite layer and the hole transport layer directly affects the performance and stability of the device, especially the improvement of the charge transfer efficiency and interface contact of the buried interface, which is crucial to improving the efficiency of perovskite solar cells. Although traditional interface modification methods, such as the use of hole transport materials, can improve device performance to a certain extent, there are still challenges in terms of interface stability and long-term efficiency maintenance.
[0003] Self-assembled monolayers (SAMs) have been widely used in interface modification and charge transfer optimization because they can spontaneously form ordered and stable molecular layers on the surfaces of different materials. By adjusting the chemical composition and structure of SAM molecules, the interface properties between perovskite and electrodes can be effectively improved. However, how to more effectively bond the self-assembled monolayer to the perovskite material and improve the interface quality remains a difficult point in current research. Summary of the invention
[0004] In order to solve the above technical problems, the primary purpose of the present invention is to provide a perovskite photovoltaic device based on conductive adhesive bonding.
[0005] Another object of the present invention is to provide a method for preparing a perovskite photovoltaic device based on conductive adhesive bonding.
[0006] The present invention is achieved through the following technical solutions:
[0007] A perovskite photovoltaic device based on conductive adhesive bonding comprises an anode substrate, a self-assembled monolayer, a conductive adhesive layer, a perovskite layer, an electron transport layer, a hole blocking layer and a cathode electrode arranged in sequence on one side of the anode substrate, wherein the material of the conductive adhesive layer is selected from one or more of polyaniline, polythiophene, polypyrrole and polyacetylene.
[0008] The present invention adopts a conductive glue with strong adhesion and high conductivity to construct an adhesive bridge between the self-assembled monolayer and the perovskite layer, and utilizes the passivating groups of the conductive glue to passivate the buried interface defects in the perovskite. The π-π interaction between the molecules and the self-assembled monolayer promotes charge transfer and optimizes the buried interface contact.
[0009] Furthermore, the molecular weight of the material of the conductive adhesive layer is 50,000-60,000 Da.
[0010] Furthermore, the material of the self-assembled monolayer is selected from one or more of 2-phenylcarbazoleethylphosphonic acid, (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid, (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid and 4-(3,6-dimethoxycarbazole-9-yl)butylphosphonic acid.
[0011] A method for preparing the above-mentioned perovskite photovoltaic device based on conductive adhesive bonding comprises the following steps:
[0012] S1. Preparing a self-assembled monolayer on an anode substrate;
[0013] S2. Preparing a conductive adhesive layer on the self-assembled monolayer described in S1;
[0014] S3. Preparing a perovskite layer on the conductive adhesive layer described in S2;
[0015] S4. Preparing an electron transport layer on the perovskite layer described in S3;
[0016] S5. Prepare a hole blocking layer and a cathode electrode in sequence on the electron transport layer described in S4 to obtain the perovskite photovoltaic device based on conductive adhesive bonding.
[0017] The present invention realizes the preparation of high-efficiency perovskite photovoltaic devices by bonding the self-assembled monolayer and the perovskite layer interface with conductive adhesive. The conductive adhesive molecules not only provide stable physical bonding, but also enhance the charge transfer efficiency of the interface, thereby improving the photoelectric conversion efficiency of the perovskite photovoltaic device. Compared with the traditional interface treatment method, the use of conductive adhesive can effectively reduce the interface defects between the perovskite layer and the self-assembled monolayer, thereby significantly improving the overall performance of the photovoltaic device.
[0018] Furthermore, in step S1, the anode substrate includes an indium tin oxide (ITO) substrate.
[0019] In a specific implementation, the ITO substrate is cleaned, dried, and subjected to ultraviolet treatment, and the resulting ITO substrate has excellent conductivity, light transmittance, and flatness.
[0020] Furthermore, in step S1, the preparation of the self-assembled monolayer includes the following steps: spin coating the self-assembled monolayer solution on the anode substrate at 2500-3500 rpm, and annealing at 90-110° C. to obtain the self-assembled monolayer.
[0021] Furthermore, the preparation method of the self-assembled monomolecule solution is: dissolving the self-assembled monomolecule in an organic solvent to obtain the self-assembled monomolecule solution.
[0022] Furthermore, the organic solvent is preferably ethanol.
[0023] Furthermore, the spin coating time is 20 to 40 seconds.
[0024] Furthermore, the annealing treatment time is 8 to 12 minutes.
[0025] Furthermore, in step S2, the preparation of the conductive adhesive layer includes the following steps: dissolving the conductive adhesive in an organic solvent to obtain a conductive adhesive solution; and coating the conductive adhesive solution on the self-assembled monolayer.
[0026] Furthermore, the organic solvent is preferably N-methylpyrrolidone (NMP).
[0027] Furthermore, the concentration of the conductive adhesive in the conductive adhesive solution is 0.05-0.5 mg / mL.
[0028] In a specific implementation manner, the conductive glue is dissolved in an organic solvent and stirred at 50-60° C. for 1-2 hours to obtain a conductive glue solution.
[0029] Furthermore, in step S2, the conductive adhesive solution is spin-coated on the self-assembled monolayer, and the conductive adhesive layer is obtained after annealing.
[0030] Furthermore, the spin coating speed is 3500-4500 rpm, and the spin coating time is 15-30 s.
[0031] Furthermore, the annealing treatment is performed at a temperature of 90-110°C.
[0032] Furthermore, the annealing treatment time is 4 to 6 minutes.
[0033] Furthermore, in step S3, the preparation of the perovskite layer includes the following steps: dissolving lead iodoformamide (FAPbI3) in an organic solvent to obtain a perovskite solution; and coating the perovskite solution on the conductive adhesive layer.
[0034] Furthermore, the organic solvent is dimethylformamide (DMF) and / or dimethyl sulfoxide (DMSO). When DMF and DMSO are used as a mixed solvent, the volume ratio of DMF to DMSO is 4:1.
[0035] In a specific embodiment, FAPbI3 is dissolved in an organic solvent and stirred at 50-60°C for 5-6 hours to obtain a perovskite solution.
[0036] Furthermore, the solid-liquid ratio of the FAPbI3 to the organic solvent is (600-800) mg:1 mL.
[0037] Furthermore, an additive is added to the perovskite solution, and the additive may be methyl ammonium chloride (MACl).
[0038] Furthermore, the mass ratio of the FAPbI3 to the additive is (60-80):1.
[0039] Furthermore, in step S2, the perovskite solution is spin-coated on the conductive adhesive layer, and the perovskite layer is obtained after annealing.
[0040] Furthermore, the spin coating has a rotation speed of 5500-6500 rpm, and the anti-solvent is added 25-30 seconds after the start of the spin coating, and the spin coating is continued for 25-30 seconds before annealing at 90-110° C. for 20-30 minutes.
[0041] Further, the anti-solvent comprises chlorobenzene (CB).
[0042] Furthermore, in step S4, the electron transport layer is prepared by spin coating, the spin coating speed is 1500-2500 rpm, and the spin coating time is 20-40 s.
[0043] Furthermore, the material of the electron transport layer includes fullerene derivatives (PCBM).
[0044] Furthermore, in step S5, a hole blocking layer and a cathode electrode are prepared in sequence by using a thermal evaporation deposition method.
[0045] Furthermore, the material of the hole blocking layer includes bathocuproine (BCP), and the cathode electrode includes a silver (Ag) electrode.
[0046] Furthermore, the thickness of the self-assembled monolayer is 5 to 10 nm, the thickness of the conductive adhesive layer is 20 to 40 nm, the thickness of the perovskite layer is 500 to 600 nm, the thickness of the electron transport layer is 30 to 40 nm, the thickness of the hole blocking layer is 8 to 10 nm, and the thickness of the cathode electrode is 100 to 110 nm.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] 1. The present invention uses conductive glue as a conductive adhesive to interact with perovskite and bond with self-assembled single molecules at the same time, improve the buried interface contact, enhance the charge transfer and stability of the interface contact, and thus significantly improve the overall performance of the photovoltaic device. The present invention provides a conductive glue bonding strategy. This interface treatment method has important application potential in the future development of high-efficiency perovskite photovoltaic devices, and provides new ideas and technical support for further improving the efficiency and stability of photovoltaic devices.
[0049] 2. The perovskite photovoltaic device based on conductive adhesive bonding provided by the present invention has a photoelectric conversion efficiency (PCE) of up to 25.59% under sunlight with an atmospheric mass (AM) of 1.5G; after 1200 hours of aging under air conditions and light-emitting diode illumination, it still maintains an initial efficiency of 97.3%, and has excellent performance and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 Schematic diagram of the structure of the perovskite photovoltaic device of Example 1 and a schematic diagram of the conductive adhesive bonding mechanism.
[0051] Figure 2 DLCP curves of the perovskite photovoltaic devices of Example 1 and Comparative Example 1.
[0052] Figure 3 1 is a conductivity test curve diagram of the perovskite photovoltaic device of Example 1 and Comparative Example 1.
[0053] Figure 4 It is a JV test curve diagram of the perovskite photovoltaic devices of Examples 1 to 4 and Comparative Example 1 under AM 1.5G sunlight irradiation.
[0054] Figure 5 EQE and integrated current curves of the perovskite photovoltaic devices of Example 1 and Comparative Example 1.
[0055] Figure 6 The PCE attenuation curves of the perovskite photovoltaic devices of Example 1 and Comparative Example 1 under air conditions and light-emitting diode illumination. DETAILED DESCRIPTION
[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0057] The present invention provides a perovskite photovoltaic device based on conductive adhesive bonding, comprising an anode substrate, a self-assembled monolayer, a conductive adhesive layer, a perovskite layer, an electron transport layer, a hole blocking layer and a cathode electrode arranged in sequence on one side of the anode substrate, wherein the material of the conductive adhesive layer is selected from one or more of polyaniline, polythiophene, polypyrrole and polyacetylene.
[0058] The present invention also provides a method for preparing a perovskite photovoltaic device based on conductive adhesive bonding, comprising the following steps:
[0059] S1. Preparing a self-assembled monolayer on an anode substrate;
[0060] S2. Preparing a conductive adhesive layer on the self-assembled monolayer described in S1;
[0061] S3. Preparing a perovskite layer on the conductive adhesive layer described in S2;
[0062] S4. Preparing an electron transport layer on the perovskite layer described in S3;
[0063] S5. A hole blocking layer and a cathode electrode are sequentially prepared on the electron transport layer described in S4 to obtain the perovskite photovoltaic device.
[0064] In a specific embodiment, the preparation method comprises the following steps:
[0065] S1. Cleaning the ITO substrate, drying the cleaned ITO substrate, and after UV treatment, spin coating the self-assembled monolayer solution on the ITO substrate to obtain a self-assembled monolayer;
[0066] S2. Spin-coating the conductive adhesive solution on the self-assembled monolayer, and annealing to obtain the conductive adhesive layer;
[0067] S3. Spin-coating the perovskite solution on the conductive adhesive layer, and annealing to obtain the perovskite layer;
[0068] S4. preparing an electron transport layer on the perovskite layer by spin coating;
[0069] S5. A hole blocking layer and a cathode electrode are sequentially prepared on the electron transport layer by a thermal evaporation deposition method to obtain the perovskite photovoltaic device based on conductive adhesive bonding.
[0070] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0071] Unless otherwise specified, the experimental methods used in the following examples and comparative examples are all conventional methods, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0072] The ITO substrate, formamidinium lead iodide (FAPbI3) and methylammonium chloride (MACl) used in the following examples and comparative examples were purchased from Liaoning Advanced Election Technology Co., Ltd. Dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), ethanol and N-methylpyrrolidone (NMP) were purchased from Alfa Aesar Ltd. Conductive glue (polyaniline, polythiophene, polypyrrole, polyacetylene) with a molecular weight of 50,000 to 60,000 Da was purchased from Macklin Ltd.
[0073] In the following examples and comparative examples, the preparation method of the perovskite solution is as follows: 679 mg FAPbI3 and 10 mg MACl are dissolved in 1 mL of a mixed solvent of DMF and DMSO, wherein the volume ratio of DMF to DMSO is 4:1, and the perovskite solution is obtained by stirring at 60°C for 6 hours.
[0074] Example 1
[0075] A perovskite photovoltaic device with an inverted structure of ITO / MeO-2PACz / PANI / Perovskite / PCBM / BCP / Ag based on conductive adhesive bonding, comprising an ITO substrate, a MeO-2PACz layer, a PANI layer, a Perovskite layer, a PCBM layer, a BCP layer and an Ag electrode sequentially arranged on one side of the ITO substrate, and is specifically prepared by the following method:
[0076] S1. Prepare a 10nm MeO-2PACz layer on an ITO substrate: dissolve 0.5mg MeO-2PACz in 1mL ethanol to obtain a MeO-2PACz solution; repeatedly ultrasonically clean the ITO substrate with deionized water and ethanol three times, then bake for 20min to completely remove the solvent and moisture, treat with ultraviolet light and ozone for 25min, and statically coat 70μl of MeO-2PACz solution. Spin coat the MeO-2PACz solution on the ITO substrate at 3000rpm for 30s, and anneal at 100℃ for 10min to obtain a MeO-2PACz layer.
[0077] S2. Prepare a 30 nm PANI layer on the MeO-2PACz layer described in S1: dissolve PANI in NMP and stir at 60°C for 1 h to prepare a PANI solution with a concentration of 0.1 mg / mL; add 30 μL of PANI solution onto the MeO-2PACz layer, spin coat at 4000 rpm for 30 s, and anneal at 100°C for 5 min to obtain a PANI layer.
[0078] S3. Prepare a 500nm Perovskite layer on the PANI layer described in S2: statically coat 70 microliters of perovskite solution on the PANI layer, the spin coating speed is 6000rpm, add 200μL of CB 25s after the start of spin coating, continue spin coating for 15s, then transfer to a heating table, anneal at 100°C for 30min to obtain a Perovskite layer.
[0079] S4. Prepare a 30 nm PCBM layer on the Perovskite layer described in S3: statically coat 60 μl of 20 mg / mL PCBM solution on the Perovskite layer, and spin coat at 2000 rpm for 30 s to obtain a PCBM layer.
[0080] S5. A BCP layer and an Ag electrode are sequentially prepared on the PCBM layer described in S4: an 8 nm BCP layer and a 100 nm Ag electrode are sequentially prepared by thermal evaporation deposition.
[0081] Example 2
[0082] A perovskite photovoltaic device with an inverted structure of ITO / Me-4PACz / PANI / Perovskite / PCBM / BCP / Ag based on conductive adhesive bonding, comprising an ITO substrate, a Me-4PACz layer, a PANI layer, a Perovskite layer, a PCBM layer, a BCP layer and an Ag electrode sequentially arranged on one side of the ITO substrate, and is specifically prepared by the following method:
[0083] S1. Prepare a 10nm Me-4PACz layer on an ITO substrate: dissolve 0.5mg Me-4PACz in 1mL ethanol to obtain a Me-4PACz solution; repeatedly ultrasonically clean the ITO substrate three times with deionized water and ethanol, then bake for 20min to completely remove the solvent and moisture, treat with ultraviolet light and ozone for 25min, statically coat 70μl of Me-4PACz solution, spin coat the Me-4PACz solution on the ITO substrate at 3000rpm for 30s, and anneal at 100℃ for 10min to obtain a Me-4PACz layer.
[0084] S2. Prepare a 30 nm PANI layer on the Me-4PACz layer described in S1: dissolve PANI in NMP and stir at 60°C for 1 h to prepare a PANI solution with a concentration of 0.1 mg / mL; add 30 μL of PANI solution onto the Me-4PACz layer, spin coat at 4000 rpm for 30 s, and anneal at 100°C for 5 min to obtain a PANI layer.
[0085] S3. Prepare a 500nm Perovskite layer on the PANI layer described in S2: statically coat 70 microliters of perovskite solution on the PANI layer, the spin coating speed is 6000rpm, add 200μL of CB 25s after the start of spin coating, continue spin coating for 15s, then transfer to a heating table, anneal at 100°C for 30min to obtain a Perovskite layer.
[0086] S4. Prepare a 30 nm PCBM layer on the Perovskite layer described in S3: statically coat 60 μl of 20 mg / mL PCBM solution on the Perovskite layer, and spin coat at 2000 rpm for 30 s to obtain a PCBM layer.
[0087] S5. A BCP layer and an Ag electrode are sequentially prepared on the PCBM layer described in S4: an 8 nm BCP layer and a 100 nm Ag electrode are sequentially prepared by thermal evaporation deposition.
[0088] Example 3
[0089] A perovskite photovoltaic device with an inverted structure of ITO / MeO-2PACz / PTH / Perovskite / PCBM / BCP / Ag based on conductive adhesive bonding, comprising an ITO substrate, a MeO-2PACz layer, a PTH layer, a Perovskite layer, a PCBM layer, a BCP layer and an Ag electrode sequentially arranged on one side of the ITO substrate, and is specifically prepared by the following method:
[0090] S1. Prepare a 10nm MeO-2PACz layer on an ITO substrate: dissolve 0.5mg MeO-2PACz in 1mL ethanol to obtain a MeO-2PACz solution; repeatedly ultrasonically clean the ITO substrate with deionized water and ethanol three times, then bake for 20min to completely remove the solvent and moisture, treat with ultraviolet light and ozone for 25min, and statically coat 70μl of MeO-2PACz solution. Spin coat the MeO-2PACz solution on the ITO substrate at 3000rpm for 30s, and anneal at 100℃ for 10min to obtain a MeO-2PACz layer.
[0091] S2. Prepare a 30 nm PTH layer on the MeO-2PACz layer described in S1: dissolve PTH in NMP and stir at 60°C for 1 h to prepare a PTH solution with a concentration of 0.1 mg / mL; add 30 μL of PTH solution on the MeO-2PACz layer, spin coat at 4000 rpm for 30 s, and anneal at 100°C for 5 min to obtain the PTH layer.
[0092] S3. Prepare a 500nm Perovskite layer on the PTH layer described in S2: statically coat 70 microliters of perovskite solution on the PTH layer, the spin coating speed is 6000rpm, add 200μL of CB 25s after the start of spin coating, continue spin coating for 15s, then transfer to a heating table, anneal at 100°C for 30min to obtain a Perovskite layer.
[0093] S4. Prepare a 30 nm PCBM layer on the Perovskite layer described in S3: statically coat 60 μl of 20 mg / mL PCBM solution on the Perovskite layer, and spin coat at 2000 rpm for 30 s to obtain a PCBM layer.
[0094] S5. A BCP layer and an Ag electrode are sequentially prepared on the PCBM layer described in S4: an 8 nm BCP layer and a 100 nm Ag electrode are sequentially prepared by thermal evaporation deposition.
[0095] Example 4
[0096] A perovskite photovoltaic device with an inverted structure of ITO / Me-4PACz / PTH / Perovskite / PCBM / BCP / Ag based on conductive adhesive bonding, comprising an ITO substrate, a Me-4PACz layer, a PTH layer, a Perovskite layer, a PCBM layer, a BCP layer and an Ag electrode sequentially arranged on one side of the ITO substrate, and is specifically prepared by the following method:
[0097] S1. Prepare a 10nm Me-4PACz layer on an ITO substrate: dissolve 0.5mg Me-4PACz in 1mL ethanol to obtain a Me-4PACz solution; repeatedly ultrasonically clean the ITO substrate three times with deionized water and ethanol, then bake for 20min to completely remove the solvent and moisture, treat with ultraviolet light and ozone for 25min, statically coat 70μl of Me-4PACz solution, spin coat the Me-4PACz solution on the ITO substrate at 3000rpm for 30s, and anneal at 100℃ for 10min to obtain a Me-4PACz layer.
[0098] S2. Prepare a 30 nm PTH layer on the Me-4PACz layer described in S1: dissolve PTH in NMP and stir at 60°C for 1 h to prepare a PTH solution with a concentration of 0.1 mg / mL; add 30 μL of PTH solution on the Me-4PACz layer, spin coat at 4000 rpm for 30 s, and anneal at 100°C for 5 min to obtain the PTH layer.
[0099] S3. Prepare a 500nm Perovskite layer on the PTH layer described in S2: statically coat 70 microliters of perovskite solution on the PTH layer, the spin coating speed is 6000rpm, add 200μL of CB 25s after the start of spin coating, continue spin coating for 15s, then transfer to a heating table, anneal at 100°C for 30min to obtain a Perovskite layer.
[0100] S4. Prepare a 30 nm PCBM layer on the Perovskite layer described in S3: statically coat 60 μl of 20 mg / mL PCBM solution on the Perovskite layer, and spin coat at 2000 rpm for 30 s to obtain a PCBM layer.
[0101] S5. A BCP layer and an Ag electrode are sequentially prepared on the PCBM layer described in S4: an 8 nm BCP layer and a 100 nm Ag electrode are sequentially prepared by thermal evaporation deposition.
[0102] Comparative Example 1
[0103] A perovskite photovoltaic device with an inverted structure of ITO / MeO-2PACz / Perovskite / PCBM / BCP / Ag, comprising an ITO substrate, a MeO-2PACz layer, a Perovskite layer, a PCBM layer, a BCP layer and an Ag electrode sequentially arranged on one side of the ITO substrate, and is specifically prepared by the following method:
[0104] S1. Prepare a MeO-2PACz layer on an ITO substrate: dissolve MeO-2PACz in ethanol to obtain a MeO-2PACz solution; repeatedly ultrasonically clean the ITO substrate three times with deionized water and ethanol, then bake for 20 minutes to completely remove the solvent and moisture, treat with ultraviolet light and ozone for 25 minutes, statically coat 70 microliters of MeO-2PACz solution, spin coat the MeO-2PACz solution on the ITO substrate at a speed of 3000 rpm for 30 seconds, and anneal at 100°C for 10 minutes to obtain a MeO-2PACz layer.
[0105] S2. Prepare a Perovskite layer on the MeO-2PACz layer described in S1: statically coat 70 μL of perovskite solution on the MeO-2PACz layer at a spin coating speed of 6000 rpm, add 200 μL of CB 25 seconds after the start of spin coating, continue spin coating for 15 seconds, then transfer to a heating table and anneal at 100°C for 30 minutes to obtain a Perovskite layer.
[0106] S3. Preparation of a PCBM layer on the Perovskite layer described in S2: 60 μl of PCBM solution was statically coated on the Perovskite layer, and spin-coated at a rotation speed of 2000 rpm for 30 seconds to obtain a PCBM layer.
[0107] S4. A BCP layer and an Ag electrode are sequentially prepared on the PCBM layer described in S3: an 8 nm BCP layer and a 100 nm Ag electrode are sequentially prepared by thermal evaporation deposition.
[0108] The performance of the perovskite photovoltaic devices of Example 1 and Comparative Example 1 was tested using a programmable Keithley 2400 source under AM 1.5G illumination (100 mW / cm 2 ) The current density-voltage (JV) curves of the perovskite photovoltaic device were tested under . The driver level capacitance analysis (DLCP) test was performed using a Keithley 4200SCS and a probe station. The external quantum efficiency (EQE) was measured using a system consisting of a xenon lamp, a monochromator, a chopper, a lock-in amplifier, and a calibrated silicon photodetector.
[0109] Figure 1 The schematic diagram of the structure of the perovskite photovoltaic device and the schematic diagram of the conductive adhesive bonding mechanism of Example 1. The incorporation of conductive adhesive molecules plays an important role in optimizing the interface contact between the perovskite layer and the self-assembled monolayer. The combination of the conductive adhesive molecules and the perovskite improves the interfacial bonding with the self-assembled monolayer, and the π-π interaction between the conductive adhesive molecules and the self-assembled monolayer promotes charge transfer.
[0110] Figure 2 DLCP curves of the perovskite photovoltaic devices of Example 1 and Comparative Example 1, from Figure 2 It can be seen that the DLCP curves of the untreated perovskite photovoltaic device in Comparative Example 1 and the perovskite photovoltaic device treated with conductive adhesive in Example 1 have considerable overlap on the left side (representing the upper interface defect), indicating that the conductive adhesive treatment has little effect on the upper interface defect. However, the curve corresponding to the photovoltaic device treated with conductive adhesive on the right side is significantly lower than that of the untreated photovoltaic device, indicating that the conductive adhesive treatment reduces the buried interface defect density, thereby improving the buried interface quality.
[0111] Figure 3 The conductivity test curves of the perovskite photovoltaic devices of Example 1 and Comparative Example 1 are shown in FIG. Figure 3 It can be seen that the conductivity of the hole transport layer is significantly improved after being treated with conductive glue, indicating that modifying the interface with conductive glue is more conducive to promoting hole migration at the buried interface.
[0112] Figure 4 The JV test curves of the perovskite photovoltaic devices of Examples 1 to 4 and Comparative Example 1 under the sunlight of AM 1.5G are shown in FIG. Figure 4 It can be seen that the highest PCE of the untreated perovskite photovoltaic device in comparative example 1 and the perovskite photovoltaic device treated with conductive adhesive in example 1 reached 20.59% and 25.59% respectively, and the performance of the optimized photovoltaic device was significantly improved. At the same time, the PCE of 25.59% is also one of the highest inverted perovskite photovoltaic device efficiencies reported so far.
[0113] Figure 5 EQE and integrated current curves of the perovskite photovoltaic devices of Example 1 and Comparative Example 1. Figure 5 It can be seen that the integrated current density of the untreated perovskite photovoltaic device in comparative example 1 is 23.91 mA / cm 2 , while the integrated current density of the perovskite photovoltaic device treated with the conductive adhesive in Example 1 was increased to 24.43 mA / cm 2 At the same time, the improvement of EQE brings higher actual device current density.
[0114] Figure 6 The PCE attenuation curves of the perovskite photovoltaic devices of Example 1 and Comparative Example 1 under air conditions and light-emitting diode illumination are shown in FIG. Figure 6 It can be seen that after 1200 hours of aging, the untreated perovskite photovoltaic device in comparative example 1 showed rapid degradation, and the efficiency dropped to 76.4% of the original after 1200 hours. In contrast, the perovskite photovoltaic device treated with conductive adhesive in Example 1 maintained 97.3% of the original efficiency at the same time, indicating that the perovskite photovoltaic device treated with conductive adhesive showed better stability.
[0115] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A perovskite photovoltaic device based on conductive adhesive bonding, characterized in that: The invention comprises an anode substrate, a self-assembled monolayer, a conductive adhesive layer, a perovskite layer, an electron transport layer, a hole blocking layer and a cathode electrode which are sequentially arranged on one side of the anode substrate, wherein the material of the conductive adhesive layer is selected from one or more of polyaniline, polythiophene, polypyrrole and polyacetylene.
2. The perovskite photovoltaic device according to claim 1, characterized in that: The molecular weight of the material of the conductive adhesive layer is 50000-60000Da.
3. The perovskite photovoltaic device according to claim 1, characterized in that: The material of the self-assembled monolayer is selected from one or more of 2-phenylcarbazoleethylphosphonic acid, (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid, (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid and 4-(3,6-dimethoxycarbazole-9-yl)butylphosphonic acid.
4. A method for preparing a perovskite photovoltaic device based on conductive adhesive bonding according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Preparing a self-assembled monolayer on an anode substrate; S2. Preparing a conductive adhesive layer on the self-assembled monolayer described in S1; S3. Preparing a perovskite layer on the conductive adhesive layer described in S2; S4. Preparing an electron transport layer on the perovskite layer described in S3; S5. Prepare a hole blocking layer and a cathode electrode in sequence on the electron transport layer described in S4 to obtain the perovskite photovoltaic device based on conductive adhesive bonding.
5. The preparation method according to claim 4, characterized in that: In step S1, the preparation of the self-assembled monolayer includes the following steps: spin coating the self-assembled monolayer solution on the anode substrate at 2500-3500 rpm, and annealing at 90-110° C. to obtain the self-assembled monolayer.
6. The preparation method according to claim 4, characterized in that: In step S2, the preparation of the conductive adhesive layer includes the following steps: The conductive glue is dissolved in an organic solvent to obtain a conductive glue solution; and the conductive glue solution is coated on the self-assembled monomolecular layer.
7. The preparation method according to claim 6, characterized in that: The concentration of the conductive adhesive in the conductive adhesive solution is 0.05-0.5 mg / mL.
8. The preparation method according to claim 6, characterized in that: In step S2, the conductive adhesive solution is spin-coated on the self-assembled monolayer, and the conductive adhesive layer is obtained after annealing.
9. The preparation method according to claim 8, characterized in that: The rotation speed of the spin coating is 3500-4500 rpm, and the spin coating time is 15-30 s.
10. The preparation method according to claim 8, characterized in that: The temperature of the annealing treatment is 90-110°C.
Citation Information
Patent Citations
Perovskite thin film, preparation method thereof and perovskite photoelectric device
CN115835744A
Perovskite solar cell and preparation method thereof
CN117320462A
Bottom-buried interface material and flexible perovskite solar cell prepared from same
CN117342958A
Trans-perovskite solar cell, preparation method thereof and photovoltaic device
CN118019421A
Slurry for polishing copper, display device manufacturing method using the same, and display device
KR1020230116156A